2021
DOI: 10.1186/s12985-021-01632-x
|View full text |Cite
|
Sign up to set email alerts
|

Virome analysis of ticks in a forest region of Liaoning, China: characterization of a novel hepe-like virus sequence

Abstract: Background Ticks (class Arachnida, subclass Acari) are vectors of transmitting a broad range of pathogenic microorganisms, protozoa, and viruses affecting humans and animals. Liaoning Province is rich in forests where different animals and, abundant Haemaphysalis longicornis ticks exist. Methods Using viral metagenomics, we analyzed the virome in 300 Haemaphysalis longicornis ticks collected from June to August 2015 in the forested region of Liaoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…The possibility of a synergistic pathogenic effect between avirulent NDV and GyVg1 requires further investigation. Interestingly, as GyVg1 infection in ticks was reported recently, it may also be possible that the virus spreads among flocks via ticks [ 15 ]. Furthermore, Varela et al reported the detection of GyVg1 in poultry vaccines, indicating the potential role of contaminated vaccines in the spread of GyVg1 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of a synergistic pathogenic effect between avirulent NDV and GyVg1 requires further investigation. Interestingly, as GyVg1 infection in ticks was reported recently, it may also be possible that the virus spreads among flocks via ticks [ 15 ]. Furthermore, Varela et al reported the detection of GyVg1 in poultry vaccines, indicating the potential role of contaminated vaccines in the spread of GyVg1 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sauvage et al [ 8 ] identified human gyrovirus, which shares 96% nucleotide identity with GyVg1, from the skin swab of a healthy individual, indicating that GyVg1 might also infect humans. Subsequently, GyVg1 was detected in human blood samples [ 9 , 10 ], human feces [ 11 , 12 ], ferret feces [ 13 ], snakes [ 14 ], ticks [ 15 ], and dogs [ 16 ], suggesting that the virus can infect a broad range of animals.…”
Section: Introductionmentioning
confidence: 99%
“…The high-throughput sequencing technology has been widely used to investigate viromes in various species and to diagnose unknown infectious diseases. The tick viromes have been analyzed in several provinces, including Heilongjiang, Liaoning, Hebei, Henan, and Yunnan in China (21)(22)(23)(24)(25), revealing a large number of novel RNA viruses of vertebrate and invertebrate hosts. These studies also suggest that the viromes are significantly affected by the tick species and geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing technology has been widely used to investigate viromes in ticks and diagnose unknown infectious diseases. To date, tick viromes have been reported in Heilongjiang, Liaoning, Hebei, Henan, Hubei, and Yunnan provinces of China ( Meng et al, 2019 ; Zhao et al, 2020 ; Shi et al, 2021 ; Xu et al, 2021 ; Yang et al, 2021 ), revealing different tick viromes, due to tick species and geographical differences. Guangdong province of China is considered as one of the global hotspots of emerging zoonotic diseases and vector-borne diseases resulting from the specific climate, environment, and biodiversity ( Wang et al, 2008 ; Allen et al, 2017 ), but the viromes in ticks in Guangdong, southern China remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%